2009
DOI: 10.1097/meg.0b013e328324b6a2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of hepatocellular carcinoma: a systematic review

Abstract: Although very infrequent, spontaneous regression is not an extraordinary event among patients with hepatocellular carcinoma. Therefore, individual responses to any given therapy should be assessed with caution and this fact may be considered at the time of calculating sample size of pilot clinical trials of new agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 16 publications
1
48
2
Order By: Relevance
“…[7][8][9][10][11] Spontaneous tumor regression is rare, but with higher incidence of HCC compared to other cancers. 12 Two meta-analyses on spontaneous regression of primary HCC have been reported, however the mechanism of this phenomenon has not yet been identified. 12,13 Tumor hypoxia due to spontaneous hepatic artery thrombosis or rapid tumor growth, or inflammatory responses was suggested as possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11] Spontaneous tumor regression is rare, but with higher incidence of HCC compared to other cancers. 12 Two meta-analyses on spontaneous regression of primary HCC have been reported, however the mechanism of this phenomenon has not yet been identified. 12,13 Tumor hypoxia due to spontaneous hepatic artery thrombosis or rapid tumor growth, or inflammatory responses was suggested as possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Tumor hypoxia due to spontaneous hepatic artery thrombosis or rapid tumor growth, or inflammatory responses was suggested as possible mechanisms. 12,13 Approximately 85 spontaneous tumor regression cases have been reported, but only 8 cases had pathologic confirmation of microscopic viable cancer cells in suspicious hepatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis for a key role of the immune system in combating cancer is further supported by clinical observations on spontaneous regressions of tumor in humans (Bodey, 2002;del Giudice et al, 2009;Oquiñena et al, 2009) and an increased risk of some cancer development in immunodeficient patients (Jagadeesh et al, 2012;Kubica & Brewer, 2012). It has also been shown that a presence of immune cell infiltrates in cancer tissues correlate with a better prognosis (Movassagh et al, 2004;Pagès et al, 2005;Wansom et al, 2012).…”
Section: Introductionmentioning
confidence: 91%
“…This must be balanced against the observation that a previous HCC/VP patient survived for seven years after diagnosis; and the rare but reported incidence of spontaneous regression of HCC which is estimated at 0.4%. 21 …”
Section: Discussionmentioning
confidence: 99%